160k views
4 votes
Rewrite the function from vertex form to standard form. Then use either form to calculate f(1) and f(-1).

f(x) = 2(x+3)2-3​

User Objects
by
5.6k points

1 Answer

6 votes

Answer:

Standard form: (x+3)^2=1/2(y+3)

f(1) = 29

f(-1) = 5

Step-by-step explanation:

The standard form of a parabola with a directrix that is horizontal is

(x-h)=4(P)(y-k)

Using the vertex form, find the vertex, foci, and the distance from the vertex to the focus or directrix.

It's easier to use the vertex form to plug in values for x.

f(1) = 2((1)+3)^2-3

f(1) = 29

f(-1) = 2((-1)+3)^2-3

f(-1) = 5

User Miroslav Glamuzina
by
5.4k points